Joint process of laser shock polishing and imprinting for metallic nanostructure fabrication. (March 2023) - Zhang, Baocai; Yang, Haifeng; Pan, Chengfeng; Zhao, Peng
Graphical abstract: Highlights: Joint process of laser shock polishing & imprinting (LSPI) can efficiently fabricate nanostructures without any pre-process. LSPI liberates the limitation of raw material without the lubricant layer, greatly improving efficiency and reducing cost. LSP and LSI techniques are similar in principle, thus can be performed with the same set of equipment. The nanostructures fabricated by LSPI have higher forming accuracy, integrity and uniformity compared to LSI technique. Abstract: Most fabrication methods of metallic nanostructures are time-consuming with multi-steps, which are difficult to achieve low-cost batch processing. In this study, joint laser process of laser shock polishing & imprinting (LSPI) is proposed to efficiently fabricate large-area nanostructures on the surface of cheap industrial aluminum foil without any pre-processing step. LSPI tailors the laser parameters of single laser manufacturing equipment to apply laser shock polishing (LSP) to polish the aluminum foil, and then laser shock imprinting (LSI) to obtain nanostructures with high accuracy, integrity and uniformity. This unique characteristic of proposed LSPI is enabled by pre-taking LSP process to improve the yield of following LSI process through significantly decreasing the surface roughness of aluminum foil. LSPI also reduces the aluminum residue inside the silicon mold, which improves the integrity of resultant nanostructure and facilitates the reuse of the mold. The working mechanism of LSPI are also investigated to reveal its fundamental fabrication principle, which may inspire other low-cost and efficient batch fabrication method for metallic nanostructures manufacturing in the future.